PENGARUH KERJASAMA TIM DAN PELATIHAN PEGAWAI TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PUSAT STATISTIK KABUPATEN BULELENG - Sukma Ningsih, Luh Merta; Sari Sanjaya, Ni Made Wulan (Jurnal Daya Saing, 2024)
This research aims to determine the effect of teamwork on employee performance and employee training on employee performance at the Buleleng Regency Central Bureau of Statistics Office. The method used in this research is quantitative using data obtained from questionnaires. The sample in this research was 33 people or all employees of the Buleleng Regency Central Statistics Agency. The data analysis technique uses multiple linear regression. The research results show that: (1) Teamwork has a positive and significant effect on employee performance. (2) Employee Training has no effect on Employee Performance.(3) Teamwork